PROJECT EVALUATION IN AN ISLAMIC PERSPECTIVE: SURVEY OF SELECTED LITERATURE - Muqorobin, Masyhudi; Bintoro, Muchamad Imam (Jurnal Ekonomi & Studi Pembangunan, 2005)
Controversy over some issues in Islamic economics of project evaluation centers basically around the role of interest as a determining-basis for discount rates, because of the interest prohibition in Islam. Apart from the question of the discount rates, the issue of incorporating social costs and benefits into any scheme of evaluation becomes especially important in the Islamic perspective. This paper reviews 30 books and selected papers on the relevant subject, and establishes three main findings. First, unlike mainstream position that relies on Fisherâ€™s work, Islamic economics conceives time preference as not a mere consumption phenomenon, but rather of production. This finding perceives this mainstream concept as the â€œfallacyâ€ of Fisherian approach Related with goods and resources, they are endowed to all human being, therefore, all resources (and all goods) are perceived initially as public goods, and satisfy both the criteria of public goods (non-rivalry and non-exclusion) to human being. Private ownership is lawful under Islmically legitimate means so that public goods, externality, and other related concepts are perceived differently from those in conventional economics. Finally, the basic difference between Islamic and conventional economics is that human behavior in Islam is imbued by ethical values. This difference necessitates different methodological justification in project evaluation. As such part two attempts to provide some departures from the conventional approach.